2003
DOI: 10.1097/00008469-200312000-00006
|View full text |Cite
|
Sign up to set email alerts
|

An earlier age of breast cancer diagnosis related to more frequent use of antiperspirants/deodorants and underarm shaving

Abstract: Breast cancer incidence suggests a lifestyle cause. A lifestyle factor used near the breast is the application of antiperspirants/deodorants accompanied by axillary shaving. A previous study did not support a link with breast cancer. If these habits have a role in breast cancer development, women using antiperspirants/deodorants and shaving their underarms frequently would be expected to have an earlier age of diagnosis than those doing so less often. An earlier age of diagnosis would also be expected in those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(97 citation statements)
references
References 35 publications
0
91
0
5
Order By: Relevance
“…Analysis of the annual quadrant incidence of breast cancer in Britain published in 2005 showed not only that there were now 54% of breast cancers in the upper outer quadrant (subdivision of the breast into four quadrants and a central nipple area would be expected to give no more than 20% in each region from random distribution), but that the relative proportion in that region had risen linearly on an annual basis since 1979 (Darbre, 2005a). This is inconsistent with the dogma that the high incidence of breast cancer in the upper outer quadrant of the breast relates solely to the slightly greater amount of breast epithelial tissue in that region but would be consistent with the increasing use of cosmetic products in the underarm area (McGrath, 2003). Studies published in 2004 further challenged this dogma by showing increased levels of genomic instability in outer regions of the human breast in histologically normal tissue (Ellsworth et al, 2004a).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Analysis of the annual quadrant incidence of breast cancer in Britain published in 2005 showed not only that there were now 54% of breast cancers in the upper outer quadrant (subdivision of the breast into four quadrants and a central nipple area would be expected to give no more than 20% in each region from random distribution), but that the relative proportion in that region had risen linearly on an annual basis since 1979 (Darbre, 2005a). This is inconsistent with the dogma that the high incidence of breast cancer in the upper outer quadrant of the breast relates solely to the slightly greater amount of breast epithelial tissue in that region but would be consistent with the increasing use of cosmetic products in the underarm area (McGrath, 2003). Studies published in 2004 further challenged this dogma by showing increased levels of genomic instability in outer regions of the human breast in histologically normal tissue (Ellsworth et al, 2004a).…”
Section: Introductionmentioning
confidence: 92%
“…Accurate reporting could have been ascertained from a group of subjects who had never used any such products, but unfortunately such a group was not included in the study. By contrast, McGrath (2003) addressed the issue of frequency (intensity) of underarm product use within a cohort of breast cancer patients and their age of diagnosis, and reported that frequency and earlier use of antiperspirant/deodorants together with underarm shaving were associated with an earlier age of breast cancer diagnosis (up to 19 years earlier). Neither study identi¼es particular chemicals/ingredients in the vast range of products that can be used.…”
Section: Regulatory Status Of Parabensmentioning
confidence: 99%
See 1 more Smart Citation
“…up to 100,000-fold lower than those found in antiperspirants, and in the range of those recently measured in the human breast, results in loss of contact inhibition and anchorage-independent growth. This finding should serve as a sentinel warning that environmental Al exposures [252] from dietary [300], parenteral [301], and topical sources [302], may have oncogenic [299,303] and epigenetic [245,253] consequences.…”
Section: Breast Cancermentioning
confidence: 99%
“…However, according to available studies, they can be harmful to the consumer due to their potential to induce allergic contact dermatitis [3,19], they can produce inhibitory effects on mitochondrial respiratory capacities [16,20], and they can disrupt the human reproductive potential [16,21]. It has been suggested that the use of parabens in cosmetics may contribute to the increasing incidence of breast cancer [22][23][24][25]. Nevertheless, another study reported that parabens are safe for the human health [1-3, 5, 26-28].…”
Section: Introductionmentioning
confidence: 99%